The impact of vaccine hesitancy on psychological impairment among healthcare workers in a Total Worker Health© approach - Di Prinzio, Reparata Rosa; Ceresi, Bianca; Arnesano, Gabriele; Dosi, Alessia; Maimone, Mariarita; Vacca, Maria Eugenia; Vinci, Maria Rosaria; Camisa, Vincenzo; Santoro, Annapaola; Raponi, Massimiliano; Tomao, Paola; Vonesch, Nicoletta; et al. (Frontiers in Public Health, 2024)
Introduction Vaccination practice is a well-known individual protective measure for biological risk in healthcare. During the COVID-19 pandemic vaccine hesitancy has grown among healthcare workers (HCWs). The study aims to investigate how vaccine hesitancy influences the psychological burden experienced by healthcare workers. Methods This study aimed to explore attitudes of HCWs in acceptance or refusal of vaccinations related to the risk of psychological impairment (PI) and describe the associated occupational factors, during the seasonal flu/COVID-19 vaccination campaign of 2022–2023. 302 HCWs were enrolled in the study. A questionnaire was self-administered, including two scales on the risk of psychological impairment (Psychological Injury Risk Indicator, PIRI) and vaccine hesitancy (Adult Vaccine Hesitancy Scale, AVHS). Results PIRI scores revealed that 29.8% of participants were at risk of PI. Differences in sex, age, occupational seniority, professional category, and night shifts were found between HCWs at risk of PI and those not at risk. Females registered a four-fold higher risk than males (85.6% vs. 14.4%, χ2 = 4.450, p < 0.05). Nurses were the highest risk category, followed by physicians and technicians (54.4% vs. 30.0% vs. 12.2%, χ2 = 14.463, p < 0.001). 41.7% of participants received the flu vaccination, and 98.9% received the COVID-19 vaccine. HCWs were prone to being vaccinated to protect patients and family members. Conversely, vaccine refusal was attributed to the perception of flu vaccines as not beneficial and COVID-19 contagion at low risk. The latter was more frequently reported for HCWs at risk of PI (16.7% vs. 4.7%, χ2 = 11.882, p = 0.001). Finally, hesitant HCWs were at higher risk of psychological impairment than others. Discussion HCWs expressed vaccine acceptance considering their social role in the community as protectors. However, the underestimation of the risk of severity of COVID-19 was more relevant among HCWs at risk of PI than others. Psychological aspects need to be considered by healthcare providers when fighting vaccine hesitancy.